Anticancer potential of an exopolysaccharide from Lactobacillus helveticus MB2-1 on human colon cancer HT-29 cells via apoptosis induction. Issue 11 (9th November 2020) - Xiao, Luyao; Ge, Xiaojia; Yang, Lin; Chen, Xiaohong; Xu, Qian; Rui, Xin; Fan, Xia; Feng, Li; Zhang, Qiuqin; Dong, Mingsheng; Li, Wei
Abstract : LHEPS-1 exhibited the strongest anti-proliferation effect, prevented G1 to S transition and increased the apoptosis of human colon cancer HT-29 cells. Abstract : This study aimed at investigating the anticancer activity of an exopolysaccharide (EPS) isolated from Lactobacillus helveticus MB2-1. The crude EPS from L. helveticus MB2-1 (LHEPS) was fractionated into three fractions, namely LHEPS-1, LHEPS-2 and LHEPS-3. LHEPS-1 exhibited the most effective anti-proliferative activity, which was associated with a stronger inhibition rate and increased lactate dehydrogenase leakage of human colon cancer HT-29 cells. Flow cytometry analysis and colorimetric assay revealed that LHEPS-1 induced cell cycle arrest by preventing G1 to S transition and increased the apoptosis rate. Furthermore, LHEPS-1 enhanced the production of intracellular reactive oxygen species (ROS) and the activity of caspases-8/9/3, increased the levels of pro-apoptotic Bax and mitochondrial cytochrome c, while decreased the anti-apoptotic Bcl-2 level, indicating that LHEPS-1 might induce the apoptosis of HT-29 cells through a ROS-dependent pathway and a mitochondria-dependent pathway. These findings suggest that LHEPS-1 may be developed as an effective food and/or drug for the prevention and therapeutics of cancer, especially human colon cancer.